2007
DOI: 10.2166/wst.2007.418
|View full text |Cite
|
Sign up to set email alerts
|

SUVA as control parameter for the effective ozonation of organic pollutants in secondary effluent

Abstract: Recent research projects have shown a good suitability of the ozonation process to transform trace concentrations of most pharmaceuticals in wastewater treatment plant (WWTP) effluents. The concentrations of carbamazepine and 17 alpha-ethinylestradiol, for instance, were reduced below their detection limits by use of ozone dosages resulting in a specific ozone consumption of 0.5 mg O3/mg DOC0. At the same time a good disinfection performance was achieved. The given hygienic requirements of the EU bathing water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 8 publications
8
56
1
1
Order By: Relevance
“…Furthermore, the removal of each compound from different effluent samples of the same source treated with the same ozone dose differed considerably. This is in accordance with previous findings [6,7,10,26]. In order to determine the ozone dose that is required to achieve 90 % removal of each pharmaceutical, the data in Figure 2 were fitted with Equation 5.…”
Section: Effect Of Doc On Required Ozone Dosage For Pharmaceuticals Rsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the removal of each compound from different effluent samples of the same source treated with the same ozone dose differed considerably. This is in accordance with previous findings [6,7,10,26]. In order to determine the ozone dose that is required to achieve 90 % removal of each pharmaceutical, the data in Figure 2 were fitted with Equation 5.…”
Section: Effect Of Doc On Required Ozone Dosage For Pharmaceuticals Rsupporting
confidence: 85%
“…The integration of ozone as an additional treatment step in the existing WWTP has become a widely accepted polishing technology for removing pharmaceuticals and other micro-pollutants in wastewater effluents [5][6][7][8][9][10]. Furthermore, treatment with ozone was found to be more cost effective than UV or UV/H 2 O 2 in the removal of estrogens in effluent from biologically treated wastewater [7,11] and it is more easily applied than activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Buffle et al (2006) proposed the use of DUV to determine ozone exposure in wastewater applications after observing a first-order kinetic relationship between the two parameters. Based on this concept, Bahr et al (2007), Wert et al (2009b), and Nanaboina and Korshin (2010) developed preliminary correlations between DUV 254 and several indicator compounds and microbes. Bahr et al (2007) presented the linear regression parameters in relation to second-order ozone and OH rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept, Bahr et al (2007), Wert et al (2009b), and Nanaboina and Korshin (2010) developed preliminary correlations between DUV 254 and several indicator compounds and microbes. Bahr et al (2007) presented the linear regression parameters in relation to second-order ozone and OH rate constants. Wert et al (2009b) indicated that ozone-susceptible target compounds (i.e., k O3 > 10 3 M À1 s…”
Section: Introductionmentioning
confidence: 99%
“…SUVA as an important parameter has been used to determine the conjugation and aromaticity of DOM by many researchers. [7][8][9] The SUVA value indicates to some extent the quality of the water and the treatability of DOM by coagulation. 27 SUVA values beyond 3 L mg À1 m À1 indicate the presence of hydrophobic, humic-like and high M w organic matter, which can be easily removed by advanced coagulation.…”
Section: Geographical Locations and Water Qualitymentioning
confidence: 99%